Tanning Bed Legislation for Minors: A Comprehensive International Comparison - Katharina Diehl; Karla S. Lindwedel; Sonja Mathes; Tatiana Görig; Olaf Gefeller (MDPI AG, 2022)
Tanning beds have been classified as carcinogenic to humans. As a result, many countries have enacted laws regulating the use of commercial tanning beds, including bans for minors. However, there is no international overview of the current legal status of access restrictions for minors that provides details on their specific design regarding age limits and possible exceptions to the statutory regulation. Therefore, we performed a comprehensive web search of current tanning bed legislation for minors on the three continents North America, Australia, and Europe. Our findings regarding the existence and concrete design of access restrictions are presented graphically, using maps. We found a wide variety of different legislations. In Australia, a total ban on tanning beds exists, while in New Zealand, tanning bed use is banned for minors. In Europe, about half of the countries have implemented a strict ban for minors. In North America, we found differences in the age limit for access restrictions between the states, provinces, and territories for those regions that implemented a ban for minors. In the United States, some states have rather "soft bans" that allow use by minors with different types of parental consent. The patchwork in legislation calls for harmonization. Therefore, our comparison is an important starting point for institutions such as the World Health Organization or the European Commission to advance their goals toward a harmonization of tanning bed legislation in general and for minors in particular.